Career Support Needs of Youth: A Qualitative Analysis of the Rural Perspective - Lehr, Ron; Jeffrey, Gary (Canadian Journal of Counselling and Psychotherapy, 2007)
This study details needs identified by parents, youth and others informed about the role played by rural and remote parents in the development and identification of careers by young people. The paper presents the findings from a series of focus group interviews carried out in rural communities. A delphi-based, qualitative, "bottom up" strategy was used to identify the needs. All information presented derived directly from the rural respondents. The detailed list of needs offered reflects potential activities which both parents, schools and other community organizations might engage in to help relatively disadvantaged (in career development terms) rural youth.